The Role of Non-Pharmacological Interventions for Disrupted Sleep in the Moderate-Severe Dementia Population: A Systematic Review - del Carmen Teruel Hernández, Esther; Souto-Camba, Sonia; Antonio López Pina, José; Irina Medina-Ramírez, Raquel; Gómez- Conesa, Antonia (Journal of Alzheimer's Research and Therapy, 2024)
This study systematically reviews the literature on non-pharmacological interventions for disrupted sleep-in people meeting established criteria for moderate-severe dementia, and to analyze the methodological quality of the included studies. The PubMed, PEDro, Cochrane, Virtual Health Library, APA PsycInfo databases were searched using a systematic literature review approach to identify various types of non-pharmacological treatments that improve disrupted sleep-in subjects with moderate-severe dementia. In accordance with the inclusion criteria, eight studies were systematically reviewed and analyzed according to the type of non-pharmacological treatment carried out. This systematic review showed that 50% of the studies used bright light therapy, 12.5% ​​the use of manual therapy, and 37.5% sleep hygiene or walking or a combination of these interventions. Based on the results of the present study, although there is some evidence to support these strategies, it is not significantly supported and highlights variation in the way the interventions were delivered. Disrupted sleep is highly prevalent in people with dementia and have a negative impact on the quality of life of the sufferer and the caregiver. Non-pharmacological approaches to its treatment are increasingly popular as an alternative to drugs, whose efficacy and side effects have raised concerns among the population. Currently, there is a need to carry out more future research to establish its effectiveness and to be able to provide clear guidelines at the time of clinical practice.
Keywords: dementia; non-pharmacological interventions; physical activity; sleep; sleep disturbance